Canadian domestic export concentration, Canada, provinces and territories, inactive - Statistics Canada (Government of Canada, 2018)
This table contains 90 series, with data for years 1988 - 2016 (not all combinations necessarily have data for all years). This table contains data described by the following dimensions (Not all combinations are available): Geography (15 items: Canada; Newfoundland and Labrador; Prince Edward Island; Nova Scotia; ...); Canadian export concentration (3 items: Product; Destination market; Province of production); Statistics (2 items: Concentration ratio; Index).